Kajian Eksperimental Unjuk Kerja Model Sistem Pembangkit Listrik Menggunakan Turbin Helik Bentuk Sudu NACA 0033 - Sinaga, J B; Suudi, A; Susila, M D; Admiral, R; Sugiman, S (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2023)
This paper presents an experimental study of a power generation system model that uses a helical turbine with NACA 0033 blades. The helical turbine has a diameter of 1 meter, a length of 1.2 meters, and three blades. Each blade has a chord length of 41.8 cm and an inclination angle of 62 degrees. Tests were conducted to harness the water flow energy in the Way Tebu irrigation canal in Banjar Agung Udik Village, Tanggamus Regency. The test results show that the power generation system model, operating at water flow velocities of 0.398 m/s, 0.491 m/s, and 0.548 m/s, generates electrical power outputs of 13.705 W, 20.987 W, and 34.63 W, with corresponding efficiencies of 36.22%, 32.74%, and 34.67%.Keywords: power plants helical turbine kinetic energy